Climate Change Will Fragment Florida Stone Crab Communities - Alaerts, Lauranne; Dobbelaere, Thomas; Gravinese, Philip M.; Hanert, Emmanuel (Frontiers in Marine Science, 2022)
Many marine species have been shown to be threatened by both ocean acidification and ocean warming which are reducing survival, altering behavior, and posing limits on physiology, especially during earlier life stages. The commercially important Florida stone crab, Menippe mercenaria, is one species that is affected by reduced seawater pH and elevated seawater temperatures. In this study, we determined the impacts of reduced pH and elevated temperature on the distribution of the stone crab larvae along the West Florida Shelf. To understand the dispersion of the larvae, we coupled the multi-scale ocean model SLIM with a larval dispersal model. We then conducted a connectivity study and evaluated the impacts of climate stressors by looking at four different scenarios which included models that represented the dispersion of stone crab larvae under: 1) present day conditions as modelled by SLIM for the temperature and NEMO-PISCES for the pH, 2) SSP1-2.6 scenario (-0.037 reduction in pH and +0.5°C compared to present-day conditions), 3) SSP2-4.5 scenario(-0.15 reduction in pH and +1.5°C) and 4) SSP5-8.5 scenario (-0.375 reduction in pH and +3.5°C). Our results show a clear impact of these climate change stressors on larval dispersal and on the subsequent stone crab distribution. Our results indicate that future climate change could result in stone crabs moving north or into deeper waters. We also observed an increase in the number of larvae settling in deeper waters (defined as the non-fishing zone in this study with depths exceeding 30 m) that are not typically part of the commercial fishing zone. The distance travelled by larvae, however, is likely to decrease, resulting in an increase of self-recruitment and decrease of the size of the sub-populations. A shift of the spawning period, to earlier in the spring, is also likely to occur. Our results suggest that habitats in the non-fishing zone cannot serve as a significant source of larvae for the habitats in the fishing zone (defined as water depth< 30 m) since there is very little exchange (< 5% of all exchanges) between the two zones. These results indicate that the stone crab populations in Florida may be susceptible to community fragmentation and that the management of the fishery should consider the potential impacts of future climate change scenarios.